Education and climate change [ living and learning in interesting times - Kagawa, Fumiyo; Selby, David (New York : Routledge, 2010)
There is widespread consensus in the international scientific community that climate change is happening and that abrupt and irreversible impacts are already set in motion. This book reviews and
1. Foreword : the fatal complacency -- 2. Climate change education and communication : a critical perspective on obstacles and resistances -- 3. Go, go, go, said the bird' : sustainability-related education in interesting times -- 4. Peace learning : universalism in interesting times -- 5. Climate injustice : how should education respond? -- 6. The environment, climate change, ecological sustainability, and antiracist education -- 7. Learning in emergencies : defense of humanity for a livable world -- 8. Sustainable democracy : issues, challenges and proposals for citizenship education in an age of climate change --9. School improvement in transition : an emerging agenda for interesting times -- 10. Critique, create, and act : environmental adult and social movement learning in an era of climate change -- 11. Transforming the ecological crisis : challenges for faith and interfaith education in interesting times -- 12. Public health threats in a changing climate : meeting the challenges through sustainable health education -- 13. Weaving change : improvising global wisdom in interesting and dangerous times -- 14. Climate change education : a critical agenda for interesting times
Description based on print version record
Includes bibliographical references and index
Keywords: Climatic changes; Education -- Environmental aspects; Education -- Social aspects; Environmental education